PERTANGGUNG JAWABAN NOTARIS/PPAT TERHADAP AKTA JUAL BELI TANAH YANG MENGANDUNG CACAT MATERIL AKTA DITINJAU DARI HUKUM PIDANA (STUDI PUTUSAN MAHKAMAH AGUNG NO. 126/ PID/ B/ 2009/ PN.DUM) - HANNA MANDELA (PREMISE LAW JURNAL, 2017)
ABSTRACT The problem of sales contract in the case number 126/PID/B/2009/PN.DUM is between Notary/PPAT (Official empowered to draw up land deeds) and land owner, land purchaser, and land broker. The land owner sign an empty form of Land Sale Contract and Never makes a Power of Attorney to sell the land. Therefore, first, it is necessary to know how about the legal consequence of land sales contract which is materially defective; secondly, how about the liability of the Notary/PPAT for land sales contrct which is materially detective, viewed from criminal law; and thirdly, how about the analysis of judge’s legal consideration on the Supreme Court's Ruling No.126/PID/B/2009/PN.DUM. Keywords : Liability of Notary/PPAT, Land Sales Contract, Deed Materially Detective